Quantification of mucosal EEC in jejunum. A comparative study of IBS patients and healthy controls. (3rd May 2020) - Mohammadian, Ghazaleh; Dlugosz, Aldona; Shetye, Jayant; Lindberg, Greger
Abstract: Background: Enteroendocrine cells (EEC) have been suggested to have a role in the pathogenesis of irritable bowel syndrome (IBS). Although many studies have analysed possible numeric changes of EEC in IBS, the results differ between different studies. One reason might be due to difficulties in standardising the morphometric method. Aim: The aim of this study was to compare two different methods for counting EEC in jejunum biopsies from patients with IBS and healthy controls. Method: Fifty-one patients with IBS and 35 healthy controls were included in the study. Jejunum mucosa was procured using a Watson capsule. Slides were immunostained for serotonin and chromogranin A and then scanned digitally. The morphometry was done by counting cells per high power field (hpf) and per mm 2 after defining area of the mucosa. The two methods were compared using Bland Altman analysis. Results: There was no difference in the number of EEC in patients with IBS compared to healthy controls. The number of cells detected by per mm 2 area of mucosa were higher than number of cells per hpf. Counting EEC per high power field systematically underestimated the number of cells in the mucosal area. Conclusions: Counting cells per mm 2 mucosal area gives a better representation of the number of EEC in small bowel mucosa. The finding of no difference in EEC numbers does not imply an equal function and further studies are needed to evaluate the role, if any of EEC, in IBS.